Discovering JMP 13 (JMP, A Business Unit of SAS, 2016)
Discovering JMP 13 provides a basic introduction to using JMP. For new users of JMP, this is a great place to start. The book also includes details about importing your data into JMP, analyzing the data, and sharing the results.
"Version 13"--Cover. - "JMP Statistical discovery. From SAS"--Cover. - Includes index. - Online resource, title from PDF title page (EBSCO, viewed November 5, 2016)
Keywords: JMP (Computer file); SAS (Computer file); Mathematical statistics -- Data processing; Information visualization; Mathematical analysis; Statistique mathématique; Informatique; Visualisation de l'information; Analyse mathématique; COMPUTERS; Data Processing; Mathematical statistics; Data processing